2013
DOI: 10.1111/iju.12214
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence after robot‐assisted radical prostatectomy: Pathophysiology and intraoperative techniques to improve surgical outcome

Abstract: Abbreviations & AcronymsAbstract: Robot-assisted radical prostatectomy has been shown to have comparable and possibly improved postoperative continent rates compared with retropubic and laparoscopic radical prostatectomy. However, postoperative urinary incontinence has remained one of the most bothersome postoperative complications. The basic concept of the intraoperative technique to improve postoperative urinary continence is to maintain as normal anatomical and functional structure in the pelvis as possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 67 publications
1
76
0
2
Order By: Relevance
“…Recent advances in knowledge of pelvic structure have led to increased understanding of the urinary continence mechanism. 15 In brief, the urethral sphincter system and periurethral support system are two main mechanisms of preserving urinary continence. The external striated sphincter is the main structure maintaining urethral closure pressure greater than bladder pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in knowledge of pelvic structure have led to increased understanding of the urinary continence mechanism. 15 In brief, the urethral sphincter system and periurethral support system are two main mechanisms of preserving urinary continence. The external striated sphincter is the main structure maintaining urethral closure pressure greater than bladder pressure.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8][9] Recent studies reported that preoperative clinical factors, anatomical characteristics, and surgical techniques are significantly associated with urinary incontinence after RARP. 1,7,[10][11][12][13][14][15] Of these factors, membranous urethral length (MUL) is an important factor that directly correlates with the functional sphincter mechanism. The urethral sphincter mechanism is composed of an external striated sphincter and an internal smooth muscle layer that are both crucial to maintaining urethral closure pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic concept of the intraoperative technique to improve postoperative urinary continence is to maintain as normal anatomical and functional structure in the pelvis as possible 7) . It may be necessary to conduct three steps to realize improvement of the early return of urinary continence after 2 T. YANAGIDA et al…”
Section: Introductionmentioning
confidence: 99%
“…and reinforcement (bladder neck plication and/ or sling suspension, etc.). On the basis of these steps, further modifications during RARP should be developed to improve urinary continence and quality of life (QOL) after RARP 7) . In this review, we discuss the intraoperative techniques to improve outcomes for early return of urinary continence following RARP, and provide a critical summary of current knowledge on its outcome in the literature.…”
Section: Introductionmentioning
confidence: 99%